2015
DOI: 10.1037/a0038864
|View full text |Cite
|
Sign up to set email alerts
|

How exposure to literary genres relates to attitudes toward gender roles and sexual behavior.

Abstract: Although past research has explored the association between media of many forms (e.g., TV, music, advertising) and sexual socialization, books are 1 form of media that has largely been ignored with respect to this topic. The current study examined the relationship between lifetime exposure to different genres of text and sexual attitudes, including gender role stereotyping and sexual conservatism. We examined both broad categories of books (i.e., fiction vs. nonfiction) along with 4 separate fiction genres (do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 75 publications
2
17
1
1
Order By: Relevance
“…This is consistent with a growing body of research suggesting that character choice is related to one's actual personality (Fong, Mullin, & Mar, 2015;Park & Henley, 2007) and that self-presentational motives function online as well as in the nonvirtual environment. Indeed, although people may use online character choice in a strategic way to fulfill a certain goal or compensate for a perceived deficiency, Bullingham and Vasconcelos argue that the key motivation for a player's online presence is to recreate his or her offline self online (2013).…”
Section: Players Prefer Certain Types Of Landscapessupporting
confidence: 75%
“…This is consistent with a growing body of research suggesting that character choice is related to one's actual personality (Fong, Mullin, & Mar, 2015;Park & Henley, 2007) and that self-presentational motives function online as well as in the nonvirtual environment. Indeed, although people may use online character choice in a strategic way to fulfill a certain goal or compensate for a perceived deficiency, Bullingham and Vasconcelos argue that the key motivation for a player's online presence is to recreate his or her offline self online (2013).…”
Section: Players Prefer Certain Types Of Landscapessupporting
confidence: 75%
“…Modified versions of the ART have been used to distinguish rates of reading nonfiction and fiction (e.g., [42,43]), as well as different genres of fiction (e.g., [44,45]. As in previous studies ( [25,31]; see also [46]), here we computed two main scores based on participants' answers to the ART: proportions of correctly identified literary authors (Literary: M = .29; SD = .22) and popular authors (Popular: M = .28; SD = .21).…”
Section: Methodsmentioning
confidence: 99%
“…There is evidence that exposure to artwork (movies, literature) comprising LGBTQ themes at least temporarily reduces prejudice. For example, in a correlational study, Fong Mullin, and Mar () showed that greater exposure to fiction, but not nonfiction, was related to increased gender role egalitarianism and reduced gender role stereotyping, factors that are related to SOGIP. This research shows that reading books (in general, not necessarily related to sexual and/or gender diversity) is related to an acceptance of diversity.…”
Section: Overview Of Recent Interventionsmentioning
confidence: 99%
“…The authors suggest that this effect is due to the fact that reading fiction increases perspective‐taking (also see below). This may help to explain why other forms of media exposure (such as watching films or television) have been found to increase people's stereotypic attitudes (Fong et al., ). Reading may be different to watching films or television in that it may require more perspective‐taking, because books stimulate the reader to adopt the view of the protagonist when written from a first‐person perspective.…”
Section: Overview Of Recent Interventionsmentioning
confidence: 99%